Characteristic of palm oil methyl ester as alternative fuel - Muhammad Rizuan, Musa (2010)
The purpose of this work is to define the relationship between the fuel physical properties and the atomization characteristic of biodiesel. The spray atomization behavior was analyzed through spray parameters such as the spray tip penetration, cone angle and droplet size. Besides that, the specific heat capacity, viscosity, specific heat profile and liquid property profile is determined to define the characteristic of palm oil and also to prepare the database of palm oil. These parameters were obtained from an injector tester system and accurate prediction of spray atomization. In addition, the experimental results of biodiesel were compared with the diesel and cooking oil. It was revealed that the increase of the pressure supply (from 100 bar to 400 bar) little affects the spray liquid tip penetration. The increase of the pressure supply also increases the complete combustion. Also, biodiesel fuel evaporation actively occurred due to the increase in the pressure supply. Besides that, palm oil methyl ester possesses a high boiling point compare to diesel and this has showed that the fuel chemical structure and critical properties significantly influences the fuel properties.